Validasi Pengiriman Produk Rantai Dingin Pada Salah Satu PBF di Kota Bandung - Nabila Tahara; Rimadani Pratiwi; Rio Bahtiar; Winda Meliani Putri (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Pharmaceutical Wholesalers (PBFs) have the responsibility to ensure that the quality of pharmaceutical products is maintained in accordance with Good Drug Distribution Practices (CDOB). One of the regulated aspects is related to the control of temperature-sensitive cold chain products. Product control must ensure product quality from receipt, storage to distribution to consumers. One of the efforts to ensure product quality during the delivery process is to conduct cold chain product delivery validation which aims to ensure product delivery remains at the appropriate range for patient safety. Delivery validation is carried out using Coolbox and Polyurethane box delivery media to compare the duration of the delivery media can maintain the temperature in the appropriate range and also ensure the necessary conditioning time before the product can be transferred to the delivery media. Also used are 4 icepacks, 5 icepacks and 6 icepack variations. Temperature is monitored for 1x24 hours, 2 x 24 hours and 3 x 24 during the standard delivery process. Temperature monitoring using a thermo logger and data processing using the Testo Comfort Software Basic 5.0 app. The results showed that Polyurethane Box using 5 icepacks could maintain the longest temperature of 49 hours and 40 minutes